The spatial dimension of history: propagation of historical knowledge via open-air museums, leisure parks and motion pictures - Ickerodt, Ulf (Public Journal of Semiotics, 2008)
Man's environment is full of references to history. Archaeological sites and cultural landscapes are examples. History is a constituent of our social identity. In this sense, on a social level, it has an integrating function and helps to structure and canalize social behaviour. In this paper we shall examine, taking archaeological sites, open-air museums, leisure parks and motion pictures as examples, how this form of promotion of history works and what effect it has on society.